Палеоботанічні характеристики унікальних знахідок з археологічних розкопок (Україна) - Безусько, Л.Г. (Український ботанічний журнал, 2012)
Впервые обобщены результаты спорово-пыльцевого анализа шести уникальных единичных
образцов, отобранных во время археологических раскопок на территории Украины. Приведены их палеопалинологическая и палеоэтноботаническая характеристики. Для исследованных образцов установлены составы ископаемых палинофлор и обобщены результаты
родовой (42 таксона) и видовой (47 таксонов) идентификации пыльцевых зерен и спор. На
конкретных примерах показана перспективность использования палеопалинологических
характеристик для реконструкции картины природных и антропогенных изменений растительного покрова прошлого, полученных для единичного, но археологически четко датированного образца. Results of palynological analysis of six unique individual samples collected during archaeological excavations
in Ukraine were summarized for the first time. Palaeopalynological and paleoethnobotanical
characteristics are presented in the article. For each sample, general composition of the fossil palynoflora
was determined and results of generic (42 taxa) and specific (47 taxa) identification of pollen
grains and spores were summarized. In these patterns obtained for a single but archaeologically well
dated sample, we have shown the prospects of palaeopalynological characteristics for reconstructing a
pattern of natural and human-induced changes of vegetation structure in the past.